(untitled) (Revista Ciência Agronômica, 2015)
The residues of cover plants and crops left on the soil surface can influence decomposition, nutrient cycling and follow crop yield. The objective was to evaluate the production of dry biomass (BD), of residues decomposition rate and yield of maize and soybean grown on different soil covers. The experimental design was a randomized block scheme banded, with four covers: Brachiaria, sun hemp, pearl millet and fallow period in autumn/winter, with maize and soybean crop in the spring/summer. We evaluated BD, decomposition through bags of decomposition and yield of maize and soybeans. Pearl millet and sunhemp were the covers which produced more of BD in the fall/winter period. the rate of decomposition of plant residues in maize and soybeans is slow in the dry period and accelerated in the rainy period; maize yield was higher when grown on sunhemp and brachiaria in the years evaluated, while for soybeans there were no differences on any measured coverage; maize and soybeans have grain yields higher than the regional average when grown on different soil covers.